2018
DOI: 10.1371/journal.pone.0204412
|View full text |Cite
|
Sign up to set email alerts
|

Differences in hepatocellular carcinoma risk, predictors and trends over time according to etiology of cirrhosis

Abstract: Background and aimsHepatocellular carcinoma (HCC) risk is high in cirrhosis. We sought to describe differences in HCC risk, predictors and trends over time according to etiology of cirrhosis.MethodsWe identified 116,404 patients with cirrhosis diagnosed between 2001–2014 in the VA healthcare system and determined incident HCC cases occurring from the date of cirrhosis diagnosis until 01/31/2017. Patients were divided by cirrhosis etiology into hepatitis C virus (HCV, n = 52,671), alcoholic liver disease (ALD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 48 publications
(62 reference statements)
2
92
1
3
Order By: Relevance
“…(36) A recent retrospective cohort study used a nation-wide VA database to investigate the risk factors for HCC in patients with cirrhosis. (19) This study included 116,404 patients with cirrhosis, of whom 17,354 had NAFLD as the underlying etiology of liver disease. The annual incidence rate of HCC was 0.9% per year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(36) A recent retrospective cohort study used a nation-wide VA database to investigate the risk factors for HCC in patients with cirrhosis. (19) This study included 116,404 patients with cirrhosis, of whom 17,354 had NAFLD as the underlying etiology of liver disease. The annual incidence rate of HCC was 0.9% per year.…”
Section: Discussionmentioning
confidence: 99%
“…(17,18) There are very few studies that have evaluated the association between diabetes and HCC in patients with NASH cirrhosis, and the results of these studies were mixed. (7,19,20) Our recent study showed that diabetes was associated with 2.1-fold increased risk of HCC in non-HCV patients with cirrhosis. (20) Because of the small number of patients with NASH cirrhosis, the association between diabetes and HCC in patients with NASH cirrhosis did not reach statistical significance (hazard ratio [HR] of 2.4; 95% confidence interval [CI] = 0.6-15.8).…”
mentioning
confidence: 99%
“…We identified all patients aged 18‐64 years with cirrhosis, defined as the presence of two or more International Classification of Diseases, Ninth Revision (ICD‐9) codes for cirrhosis (571.5 or 571.2) on separate dates. Previous validation studies have demonstrated that the presence of two outpatient ICD‐9 codes improves the positive predictive value of correctly identifying cirrhosis based on a gold standard of medical record review . The ‘diagnosis date’ of cirrhosis was defined as the first ICD‐9 code present in the database.…”
Section: Methodsmentioning
confidence: 99%
“…Previous validation studies have demonstrated that the presence of two outpatient ICD-9 codes improves the positive predictive value of correctly identifying cirrhosis based on a gold standard of medical record review. 17,18 The 'diagnosis date' of cirrhosis was defined as the first ICD-9 code present in the database.…”
Section: Patient Populationmentioning
confidence: 99%
“…However, the denominator of patients with NAFLD in the catchment area of each medical centre could be in the thousands. In fact, the risk of HCC in patients with NAFLD was recently estimated to be 0.021 per 100 patient‐years, which is substantially lower than the risk in patients with cirrhosis (1‐3 per 100 patient‐years) . The sensitivity and specificity of currently available HCC screening tests (ultrasonography and serum AFP) are too low and the costs and harms of subsequent confirmatory tests for screen‐positive patients (liver biopsy, multiphasic MRI and CT) are too high for screening in pre‐cirrhotic liver disease to be a sensible and cost‐effective proposition.…”
mentioning
confidence: 99%